Metodologia de modulação space vector ótima aplicada a conversores estáticos - Zucuni, Jordan Pauleski (2023)
Power converters are main components in many electrical systems. They are composed by semiconductors switches that operate in relatively high frequency compared with the ones of interest in order to synthesize the required voltages and currents. In this context, the field of modulation arises, which refers to the adequate swtiching process in order to achieve the required variables. So, many challenges are found, since many issues arises from the modulator project. For instance, there is the problem of how to reduce the harmonic distortion in order to satisfy normative resctrictions while the reduction of the common mode voltage is required, as it is associated with undesired currents through stray capacitances of the system. Moreover, there is the problem of thow to improve these merits without increasing the switching count compared with conventional techniques. Then, among the strategies in the literature, the space vector technique can be highlighted. It shows many possibilites through the degrees of freedom that are not fully explored to increase the performace of the converter under different merits. In this technique, among the project steps, there is the design of switching sequences, where it is performed the arrangement of vectors refering to the line-to-line voltages, phase voltages and switching states. Under this subject, there is a research issue, where this work presents contributions as a methodology to construct this arrangement, including the optimization on the duty cycle distribution among vectors that appears repeatedaly in a same sample period. As long as the modulation involves many objectives as previouly mentioned, this study is developed with a multicriteria approach applying the VIKOR method. As normally there are conflicting objectives, this methodology guides the selection of the sequences in order to find the best trade-off among the required specifications. Then, this work proposes an optimal space vector methodology, generic to the topology, designing sequences with the integration of the three spaces of the converter: line-to-line voltages, phase voltages and switching states. As a consequence, this work presents the development, equations and related proposals, for instance, the reflection of the reference and comutation voltage vectors to the first sector and the algebraic validation of the candidate line sequences considered over the fundamental period horizon intead of only one sample period as normally treated in the literature. Then, athough this is a generic methodology, it is applied to three different converters in order to demonstrate the applicability and performance of the presented strategy, with practical and simulation results, including the case of normative restrictions for grid-tied photovoltaics systems, corroborating with the analysis developed over this work.